Sistem Pakar Penyakit Pencernaan Dengan Metode Case Base Reasoning (Studi Kasus : RSUD DR. H. Yuliddin Away) - Ilham safar; Aria Satria (Cattleya Darmaya Fortuna, 2020)
Digestive diseases are all diseases that occur in the channel digestion. This disease is a large group of diseases esophageal organs, stomach, duodenum first, second and third part, jejunum, ileum, colon, sigmoid colon, and rectum. Digestive disease need early prevention, in the field of computers how to anticipate can by using an expert system. Expert system is a system that can make conclusions like an expert. Expert systems have many one method is the CBR method. CBR method is a method inference based on the old case. This method can be applied in fields health and is widely implemented in the world of health one to diagnose various digestive diseases. System can do Diagnosis of the disease is based on the symptoms entered by the patient through questions the questions raised by the system and provide information about the illness suffered by the patient.